Analisis Sistem Informasi Akuntansi Siklus Pendapatan pada Industri Pertelevisian - Muhammad Ryan Fahlevi (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2019)
This study has two main objectives. The first aims to determine the application of the accounting information system procedures on the revenue cycle. Second, to determine the factors that constrain revenue cycle in thecompany. Data analysis method use disdescriptive qualitative analysis with case study approach. The analysisis done by describing the circumstances objectsordescribe real researchto identify and analyze problems faced by the Research object, and then be able to provide alternatives and suggestions of solving the problems faced. The analysisshowed that the accounting information system on there venue cycle LPP TVRI Sumsel Babel has someweaknesses, particularly in the sales procedure, billing to the customer receivables, and cashreceipts. The author provides recommendations that can be used to strengthen the control over these flaws.